1999
DOI: 10.1123/jsep.21.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Peer Relationships and Physical Activity Participation in Early Adolescence

Abstract: This study tested a model describing the relationships among perceptions of peer relationships, physical self-worth, affective responses toward physical activity, and physical activity motivation. The model was grounded in Harter’s (1978,1981a, 1986,1987) theoretical perspective, proposing that perceptions of peer relationships (i.e., friendship, peer acceptance) would predict physical activity motivation via affect and physical self-worth. Adolescents (N = 418, ages 12–15 years) completed a battery of questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
0
22

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(165 citation statements)
references
References 0 publications
8
135
0
22
Order By: Relevance
“…It is possible that sport participation constitutes the endpoint rather than the antecedent in this model. Smith's (1999) work, for example, supported a model whereby peer relationship variables (including perceived social acceptance/competence) predict physical activity motivation and behavior by way of affect. A perceived social competence -> loneliness -> sport participation pathway is analogous to this conceptual chain of events.…”
Section: Limitations and Future Directionsmentioning
confidence: 86%
“…It is possible that sport participation constitutes the endpoint rather than the antecedent in this model. Smith's (1999) work, for example, supported a model whereby peer relationship variables (including perceived social acceptance/competence) predict physical activity motivation and behavior by way of affect. A perceived social competence -> loneliness -> sport participation pathway is analogous to this conceptual chain of events.…”
Section: Limitations and Future Directionsmentioning
confidence: 86%
“…Our finding pertaining to the overall peer task-involving climate factor is consistent with previous developmental and sports psychology research on peer relationships. For example, Smith (1999) found that greater peer social acceptance and positive peer interactions were related to high levels of physical self-worth. Furthermore, Eisenberg (1997) highlighted the importance of peer influence by showing that the correlation between peer approval and self-esteem enhancement increases developmentally.…”
Section: Gender and Age Differencesmentioning
confidence: 99%
“…Research in the sport domain has been limited and has typically focused on peer acceptance, status, and popularity (Chase & Dummer, 1992;Evans & Roberts, 1987), with less research on friendship (Smith, 1999;Weiss & Smith, 1999). However, this limited research indicates that competence in sport is linked to social status, popularity, and peer acceptance (Brustad, 1993;Chase & Dummer, 1992;Evans & Roberts, 1987;Weiss & Duncan, 1992), and friendship is related to positive affect (e.g., enjoyment) in physical activity (Smith, 1999).…”
mentioning
confidence: 99%